2016
DOI: 10.3390/nu8070408
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Consumption of Green Tea as a Risk Factor for Periodontal Disease among Korean Adults

Abstract: This study was performed to assess the relationship between the amount of green tea that is consumed and periodontitis. It is based on data obtained from the Korea National Health and Nutrition Examination Survey, conducted between 2008 and 2010. A community periodontal index equal to code 3 was defined as moderate periodontitis, and code 4 was defined as severe periodontitis (n = 16,726). Consumption of green tea less than one cup per day was associated with a decreased prevalence of periodontal disease among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
2
12
0
2
Order By: Relevance
“…This discrepancy could be due to subjects, types or frequency of tea drinking. Additionally, a positive association between pesticides and T2DM has also been found in several studies (25)(26)(27) . Liu et al's study in Shanghai also proposed that more pesticide exposures among tea drinkers may be associated with an increased risk of T2DM (18) .…”
Section: Discussionsupporting
confidence: 63%
“…This discrepancy could be due to subjects, types or frequency of tea drinking. Additionally, a positive association between pesticides and T2DM has also been found in several studies (25)(26)(27) . Liu et al's study in Shanghai also proposed that more pesticide exposures among tea drinkers may be associated with an increased risk of T2DM (18) .…”
Section: Discussionsupporting
confidence: 63%
“…The prevalence of periodontitis in the general Korean population is known to be as high as 30%, making periodontal disease a major disease entity for Koreans seeking medical care. [ 22 ] The recent exponential increase in persons with diabetes among the Korean population has led to a rapid increase in the socioeconomic burden due to diabetes-related complication treatments. Together with diabetic nephropathy, diabetic retinopathy is the most common microvascular complication.…”
Section: Discussionmentioning
confidence: 99%
“…Chopra et al [106] reported that green tea supplement in addition to the nonsurgical periodontal treatment resulted in improvements in the plaque index, gingival index, bleeding during probing, and clinical attachment loss parameters, and the gingival crevicular fluid antioxidant capacity was eight times higher than the control group. In contrast to these studies, in a study conducted in adults, it was found that the consumption of less than one cup of green tea per day was associated with a decrease in the prevalence of periodontal disease, and the consumption of one or more cups of green tea per day resulted in an increase in the prevalence of moderate and severe periodontitis [107].…”
Section: Flavonoidsmentioning
confidence: 74%